Durability and Reliability of EV Batteries under Electric Utility Grid Operations: Path Dependence of Battery Degradation. Issue 5 (1st January 2018) - Dubarry, Matthieu; Baure, George; Devie, Arnaud
Abstract : Vehicle-to-grid (V2G) and Grid-to-vehicle (G2V) strategies are often cited as promising approaches to mitigate the intermittency of renewable energy on electric power grids. However, their impact on vehicle battery degradation have yet to be investigated in detail. Since battery degradation is path dependent, i.e. different usage schedules lead to different degradation mechanisms, it is essential to investigate batteries under realistic V2G and G2V scenarios. The aim of this work is to understand the effect of bidirectional charging on the degradation mechanisms of commercial Li-ion cells used in electric vehicles today. Results showed that an extra V2G step during cycle-aging accelerated capacity loss and degraded the kinetics at the negative electrode. Moreover, for all cycling duty cycles, the loss of active material at the negative electrode was higher than the loss of lithium inventory. This condition could trigger lithium plating and shorten cell lifetimes. In the calendar-aging experiments, state of charge was shown to be an important factor and interacted with temperature to accelerate the loss of active material at the positive electrode and the loss of lithium. It was also found that high state of charge values caused loss of active material at the negative electrode and kinetic limitations.